Słowacki klimat Europy Środkowej w Polsce - Buczek, Marta (Przekłady Literatur Słowiańskich, 2015)
The Slovak climate of Central Europe in Poland The article concerns Slovak literature translated into Polish in recent years, 2013 and 2014. The author focuses on the problem of the translation of contemporary Slovak literature that examines the issue of Central European identity in Central Europe. She considers the latest Slovak literary works and their reception in the Polish horizon, as well as analyses translations which in the Polish horizon play the role of mediation, and promote understanding between two cultures belonging to the common Central European circle. Recent translations of contemporary Slovak literature, including Pavol Rankov, Pavel Vilikovský, Rudolf Chmel, compliment the knowledge about Slovak culture, literature and history among Polish readers. They also raise their awareness for diverse sensitivity and ability of perception. They also inspire exploration and search for new meanings. Key words: literary translation, contemporary Slovak literature, Slovak literature in Poland, Pavol Vilikovský, Pavol Rankov, Rudolf Chmel, Tomasz Grabiński, Jacek Bukowski, publishing house Książkowe Klimaty.